Rationale for the use of "Hemoglobin nectar plus" in the treatment of erectile dysfunction - I. V. Savitsky; Yu. V. Mizevich; I. V. Miastkivska; V. I. Savitsky (Kazimierz Wielki University, 2017)
Erectile dysfunction is part of the endothelial dysfunction, which in turn is a key risk factor for vascular accidents. ErD is detected in 50% of patients with diabetes mellitus, i.e. three times more often and 10-15 years earlier than in healthy men. A real breakthrough in the treatment of ErD was the appearance on the pharmaceutical market of inhibitors of phosphodiesterase type 5. However, despite the background of unconditional effectiveness, these medicinal substances, unfortunately, have a number of side effects. First of all, they are contraindicated in patients taking organic nitrates (isosorbide mononitrate, nitroglycerin, isosorbide dinitrate), and other nitro-containing drugs that are used in the treatment of coronary heart disease. They can also lead to a sharp, uncontrolled drop in blood pressure. Goal: To study the effectiveness of anthocyanins as the drug "GEMOGLOBIN NECTAR PLUS" among patients suffering from erectile dysfunction with contraindications to standard therapy. Materials and methods. The study involved 58 men, aged 46 to 68 years, who complained of erectile dysfunction. Inclusion criteria: the diagnosis was confirmed by the MIAF questionnaire. The study involved men with a duration of erectile dysfunction of at least 3 months. The group included patients with such concomitant diseases as arterial hypertension (AH), diabetes mellitus (DM), ischemic heart disease (IHD). The choice of these criteria was because patients with cardiovascular disorders have contraindications to most drugs leading to correcting ErD. Exclusion criteria: ErD of dyshormonal etiology. The criterion was based on the results of determining the level of testosterone in the blood. To study the effectiveness of flavonoids, in particular anthocyanins, with these conditions, we chose the drug "GEMOGLOBIN NECTAR PLUS". The first stage of the study was the determination of asymmetric dimethylarginine, endothelin-1 and eNO synthase in the serum prior to the initiation of flavonoids. The second stage of the study was the determination of the test markers of endothelial dysfunction 3 months after the regular intake of anthocyanins, which are known as flavonoids. As a result of the study, we obtained data on the confirmation of the relationship between erectile dysfunction and endothelial dysfunction. It was found that the use of the drug "GEMOGLOBIN NECTAR PLUS" leads to the normalization of endothelin-1, asymmetric dimethylarginine and eNO synthase, which are generally accepted markers of functioning and condition of the endothelium. It has been proved that under the influence of the studied anthocyanin concentrate the erection processes in patients suffering from cardiovascular diseases improve, which is a contraindication to the most commonly known drugs leading to improving erection. "HEMOGLOBINE NECTAR PLUS" is an antioxidant and also has a moderate effect on reducing endothelial dysfunction, which gives it a number of advantages in patients with the aforementioned concomitant diseases.